Financial Variables and Their Effects on The Development of Bank Credit and Productive Sectors in Iraq Using a Path Analysis Model - Ali Yahya Hassan, Saif; Mahdi Abbas Al-Birmani, Salah (Journal of Economics and Administrative Sciences, 2024)
This study aims to measure and analyze the direct and indirect effects of the financial variables, namely (public spending, public revenues, internal debt, and external debt), on the non-oil productive sectors with and without bank credit as an intermediate variable, using quarterly data for the period (2004Q1–2021Q4), converted using Eviews 12. In order to measure the objective of the study, the path analysis method was used using IBM SPSS-AMOS. The study concluded that the direct and indirect effects of financial variables have a weak role in directing bank credit towards the productive sectors in Iraq, which amounted to (0.18), as a result of market risks or unstable expectations in the economy. In addition to the weak credit ratings of borrowers, this is on the one hand, and on the other hand, the majority of the credit granted by the Iraqi banking system has been directed towards the construction sector as a result of the guarantees that this sector can provide compared to other productive sectors. On the other hand, financial variables were not supportive in directing bank credit towards the development of these sectors in the country's GDP because the results reflected by the direct and indirect effects of financial variables were weak in supporting productive sectors with or without bank credit. (Especially since the local debt was competing with the private sector in obtaining bank credit, and this is called the effect of crowding out.) Paper type: Research paper.